Faktor-faktor yang Berhubungan dengan Kepatuhan Perawat dalam Melakukan Hand Hygiene di Rumah Sakit St.Theresia Jambi - Tumini; Nurhayati; Dini Suryani (Nightingale: Journal of Nursing, 2026)
Hand hygiene compliance is a crucial effort in preventing infections in healthcare facilities. Low compliance among healthcare workers remains a problem that contributes to an increased risk of nosocomial infections. This study aims to analyze the relationship between knowledge, attitude, motivation, years of service, and supervision with hand hygiene compliance among healthcare workers. This study used a quantitative design with a cross-sectional approach. The sample consisted of 50 respondents selected using total sampling technique. Data were collected using questionnaires and observation sheets. Data analysis was performed using univariate and bivariate analysis with the chi-square test. The results showed that most respondents were compliant with hand hygiene (82.0%). There were significant relationships between knowledge (p=0.000), attitude (p=0.000), motivation (p=0.009), years of service (p=0.026), and supervision (p=0.001) with hand hygiene compliance. The conclusion of this study is that all variables examined have a significant relationship with hand hygiene compliance. It is recommended that healthcare institutions enhance education, motivation, and supervision continuously to improve healthcare workers' compliance with hand hygiene.